Selection of Marine Tourism Destinations in West Kalimantan Using the Analytical Hierarchy Process Method - Susy Rosyida; Hendi Minarto (Paradigma - Jurnal Komputer dan Informatika, 2025)
Tourism in West Kalimantan offers various destinations rich in meaning and history. However, there are issues in managing tourism in this region, such as the lack of easily accessible information for tourists and the uneven distribution of visits to tourist destinations. Tourists often struggle to choose destinations that match their preferences due to the limitations of comprehensive and objective information systems. This results in some destinations becoming overcrowded while others are less visited. Technological advancements enable the development of Decision Support Systems (DSS) to address these issues and enhance decision-making in selecting tourist destinations. This research aims to develop a decision support system using the Analytical Hierarchy Process (AHP) method to simplify the decision-making process in choosing maritime tourist destinations in West Kalimantan. The primary goal of this research is to help tourists select maritime tourist destinations that best suit their preferences, improve their tourism experience, and support sustainable tourism development in West Kalimantan. This study employs the AHP method in the decision-making process. The research stages include problem identification, literature review, data collection through questionnaires, data analysis, and final weight calculation. Data were collected from 400 respondents in West Kalimantan and analyzed to determine the priority of tourist destinations based on criteria such as scenery, distance, accessibility, facilities, cleanliness, and cost. Based on AHP analysis, it was found that Temajuk Sambas is the most preferred tourist destination, followed by Temajuk Mempawah, Jawai Bahari, Samudera Indah, Pulau Lemukutan, and Tanjung Bajau. The developed decision support system provides clear guidance for tourists in selecting maritime tourist destinations in West Kalimantan according to their preferences.